Charge Shift/Recombination and Triplet Formation in a Molecular Dyad based on a Borondipyrromethene (Bodipy) and an Expanded Acridinium Cation. Issue 3 (5th January 2018) - He, Xiaoyan; Benniston, Andrew C.; Lemmetyinen, Helge; Tkachenko, Nikolai V.
Abstract: A molecular monocationic dyad comprising a borondipyrromethene (Bodipy) and an expanded planar acridinium cation was prepared. The dyad, when excited in solution by an ultrashort laser pulse, generates a charge‐shift state, where a positive charge is transferred to the Bodipy from the acridinium subunit. The process takes less than 1 ps in MeCN and around 8 ps in 1, 2‐dichloroethane. The charge‐shift state collapses, in part, back to the ground state but it also leads to partial triplet formation; the discrimination between rates for the forward and reverse processes is circa 7. Abstract : Walk the line : Coupling of a borondipyrromethene (Bodipy) to an electron‐accepting expanded acridinium cation produced a linear dyad which strongly absorbs to around λ =550 nm. Excitation of either chromophore results in an ultrafast shift of positive charge to the Bodipy and is accompanied by restoration of the ground state and localised triplet formation.